179k views
1 vote
1. Simplify f(g(x)) in terms of x if f(x) = x² - 1 and g(x) = 2 x + 3.​

User Surojit
by
5.5k points

1 Answer

4 votes

In this question, you're plugging in g(x) into f(x) to simplify.

You would plug the g(x) equation into the x variable in the f(x) equation.

Plug g(x) into f(x):

(2x+3)² - 1

Solve:

(2x+3)² - 1

Use FOIL:

F = First

O = Outsides

I = Insides

L = Last

4x² + 12x + 9 - 1

Combine like terms:

4x² + 12x + 8

Answer:

4x² + 12x + 8

User Mithuzz
by
6.2k points